Flipped classroom strategies in biology learning: A systematic literature review - Muh. Wahyudi Jasman; S. Sulisetijono; Susriyati Mahanal (University of Muhammadiyah Malang, 2024)
Biology as an integral part of science learning continues to be maximized by integrating technology into its learning design. The definite manifestation of this integration process is to achieve meaningfulness, activeness, and effectiveness of the learning carried out. The flipped classroom (FC) is gaining popularity as a pedagogical model that uses the important benefits of technology in its learning environment. FC is proven to be an effective teaching mode that empowers students' 21st-century skills, stimulates students' self-learning, and improves academic performance. The potential of the FC is interesting to explore to what extent biology welcomes the FC. The aimed of this systematic literature review is to review and analyze articles published by Scopus indexed journals. We used the keywords